FIGURAÇÕES DO INTELECTUAL MODERNISTA NA OBRA DE CYRO DOS ANJOS - RAUL GOMES DA SILVA (2023)
This thesis analyzes the figurations of the modernist intellectual in the work of Cyro dos Anjos, based on the author's journalistic texts, the letters exchanged with the poet Carlos Drummond, organized in the book Cyro & Drummond: correspondências de Cyro dos Anjos e Carlos Drummond de Andrade, by Wander Melo Miranda and Roberto Said (2012), and his three novels, Amanuense Belmiro (1937), Abdias (1945) and Montanha (1956). The aim was to point out the processes of inscription of the modernist intellectual in the collective memory, the conscious engendering of the subject, the construction and destruction of selfimages, the manipulation of his own archive as a gesture of performance and the implications of these procedures for understanding Brazilian late modernity in its plural and fragmentary aspect. It examined the role of the writer as an intellectual, the relations maintained with the state, the processes of artistic creation, taking into account the ambiguities and contradictions, the unfinished nature and erasure of intimate and autofictional writing, as well as the displacements operated on hegemonic identities and power relations. The research pointed to the diffuse and melancholic nature of intellectual performance, seen as intrinsic to the country's urban modernization process and the conflicts arising from the transit between the archaic and the modern, the rural and the urban, the regional and the cosmopolitan. This proposal was developed in dialogue with Eneida Maria de Souza (1998), (2011), Luís Bueno (2015), Leonor Arfuch (2010), Mônica Velloso (1987), Sergio Miceli (2001), Michael Löwy and Robert Sayre (2015), Edward Said (2005), Julien Benda (2007), among others.